Compositionally graded nano-sized borides in a directionally solidified nickel-base superalloy. (August 2021) - Gupta, Richa; Kumar, K.C. Hari; Prasad, M.J.N.V.; Pant, Prita
Abstract: Boron is known to influence the grain boundary microchemistry and thereby improve the mechanical performance of superalloys; however, the form in which boron exists at the grain boundary is debatable. We show from electron microscopy characterization that in a directionally solidified Ni-base superalloy boron is present in the form of nearly spherical nano-sized metal borides. We also report the existence of a gradient in composition of Cr, and W within the nano-sized boride precipitates located along the grain boundaries. These borides are present discretely and suppress the agglomeration of mostly reported M23 C6 carbides at the columnar grain boundaries. This could be a possible reason for the reported improvement in transverse creep properties of boron modified directionally solidified superalloys. Graphical abstract: Image, graphical abstract